Physical and optical properties of DCJTB dye for OLED display applications: Experimental and theoretical investigation - Kurban, M.; Gündüz, Bayram (Elsevier B.V., 2017)
In this study, 4-(dicyanomethylene)-2-tert-butyl-6-(1,1,7,7-tetramethyljulolidin-4-yl-vinyl)-4H-pyran (DCJTB) was achieved using the experimental and theoretical studies. The electronic, optical and spectroscopic properties of DCJTB molecule were first investigated by performing experimental both solution and thin film techniques and then theoretical calculations. Theoretical results showed that one intense electronic transition is 505.26 nm a quite reasonable and agreement with the measured experimental data 505.00 and 503 nm with solution technique and film technique, respectively. Experimental and simple models were also taken into consideration to calculate the optical refractive index (n) of DCJTB molecule. The structural and electronic properties were next calculated using density functional theory (DFT) with B3LYP/6-311G (d, p) basis set. UV, FT-IR spectra characteristics and the electronic properties, such as frontier orbitals, and band gap energy (Eg) of DCJTB were also recorded time-dependent (TD) DFT approach. The theoretical Eg value were found to be 2.269 eV which is consistent with experimental results obtained from solution technique for THF solvent (2.155 eV) and literature (2.16 eV). The results herein obtained reveal that solution is simple, cost-efficient and safe for optoelectronic applications when compared with film technique. © 2017 Elsevier B.V.
Keywords: Density-functional theory; Electronic properties; Optical properties; Optical techniques; Structure analysis